Petugas/Pejabat Pelindungan Data Pribadi dalam Ekosistem Perlindungan Data Pribadi: Indonesia, Uni Eropa dan Singapura - Siti Yuniarti (Bina Nusantara University, 2022)
Personal data protection regulations have been adopted by 137 countries until the beginning of 2022. In addition to creating a data protection agency, personal data protection regulations have also created new professionalism, namely personal data protection officers. The main role of the data protection officer is to ensure compliance with personal data protection regulations placing the function of a data protection officer as an important factor in the personal data protection ecosystem. It raises the question of how the role of data protection officers in the personal data protection ecosystem when it is analyzed from the attributes attached to the profession. Therefore, using the normative juridical research method, this paper attempts to describe the role of the data protection officer in the personal data protection ecosystem by analyzing the attributes attached to the profession through a comparison of the General Data Protection Regulation (GDPR) in the European Union, Personal Data Protection Act Singapore and the draft of personal data regulation in Indonesia. This paper concluded that the existence of a data protection officer is part of the data protection regulation, whether it appears as an obligation or in terms of certain conditions. Independency of the data protection officer and organizational support is essential to optimize the data protection officer’s role which has been adopted on GDPR. It also noticed the presence of data protection officers as a service to fulfill the needs of data protection officers by organizations. Further research regarding the attribute of data protection officers as studied in this paper is needed since the Indonesia personal data protection bill will impact many sectors, both private and public sectors.